KATEKIN DAUN TEH HIJAU (Camelia sinensis) TERHADAP MALONDIALDEHYDE DAN SUPER OXIDE DISMUTASE - Sukina B; Gwenny I.P; Suhartati Suhartati; Harianto N (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2013)
Recent studies have shown that Plumbum could disrupt tissue prooxidant/antioxidant balance. The green tea leaves (Camelliasinensis) is an antioxidant scavenger of free radicals and chelator of heavy metals. This study was designed to know and investigate theefficacy of Katekin from green tea leaves malondialdehid (MDA) and superoxide dismutase (SOD) activity in erythrocytes caused by oralPb administration in Wistar rats. Thirty adult male rats were divided into six (6) groups (each groups: 5 rats): K+ group (oral 33.75mg/bw Katekin), K group as a normal control, K- group (oral 15.82 mg/day lead acetate), P1 group (oral 22.5 mg/bw Katekin and 15.82mg/day lead acetate, P2 group (oral 33.75 mg/bw Katekin and 15.82 mg/day lead acetate for), and P3 group (oral 45 mg/bw/Katekinand 15.82 mg/day lead acetate) for 4 weeks. The results showed that Pb exposure induced the raised of MDA levels and decrease SODactivity in erythrocytes of rats. The administration of Katekin from green tea leaves significantly reduced MDA levels and increased SODactivity in Pb exposed erythrocytes of rats. The optimal dose of Katekin from green tea leaves as a scavenger of free radicals and chelatorof heavy metals was 22.5 mg/bw/day (P1). These results indicated that the administration of Katekin from green tea leaves may havean important role in modulating oxidative stress in Pb exposed erythrocytes, but at a higher concentration of Katekin from green tealeaves showed prooxidant activity.